Variant Signal Peptides of Vaccine Antigen, FHbp, Impair Processing Affecting Surface Localization and Antibody-Mediated Killing in Most Meningococcal Isolates - da Silva, Ronni A. G.; Karlyshev, Andrey V.; Oldfield, Neil J.; Wooldridge, Karl G.; Bayliss, Christopher D.; Ryan, Ali; Griffin, Ruth (Frontiers in Microbiology, 2019)
Meningococcal lipoprotein, Factor H binding protein (FHbp), is the sole antigen of the Trumenba vaccine (Pfizer) and one of four antigens of the Bexsero vaccine (GSK) targeting Neisseria meningitidis serogroup B isolates. Lipidation of FHbp is assumed to occur for all isolates. We show in the majority of a collection of United Kingdom isolates (1742/1895) non-synonymous single nucleotide polymorphisms (SNPs) in the signal peptide (SP) of FHbp. A single SNP, common to all, alters a polar amino acid that abolishes processing: lipidation and SP cleavage. Whilst some of the FHbp precursor is retained in the cytoplasm due to reduced binding to SecA, remarkably some is translocated and further surface-localized by Slam. Thus we show Slam is not lipoprotein-specific. In a panel of isolates tested, the overall reduced surface localization of the precursor FHbp, compared to isolates with an intact SP, corresponded with decreased susceptibility to antibody-mediated killing. Our findings shed new light on the canonical pathway for lipoprotein processing and translocation of important relevance for lipoprotein-based vaccines in development and in particular for Trumenba.